Pengembangan E-Learning Berbasis Google Sites Pada Materi Sistem Ekskresi Untuk Kelas XI SMA: (Development of Google Sites-Based E-Learning on Excretory System Material for Class XI High School) - Rialdy, Alfajar; Hamidah , Afreni; Natalia , Desfaur (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
This research aims to: develop Google Sites-based e-learning media on the material of the excretory system of grade XI high school that is valid and suitable for use in the learning process based on the results of expert validation, biology teacher assessment, and student responses through the ADDIE development model. E-learning products are developed based on the analysis of the needs of teachers and students, then validated by material experts and media experts, and tested on students. The results of the study show that the development process has succeeded in producing learning media that is suitable for use. The validation of material experts in the final stage obtained a percentage of 95% with the category